The influence of operational stress and ambiguity on Soldier shoot/don't-shoot performance - Cantelon, Julie. (Tufts University. Tisch Library., 2022)
Thesis (Ph.D.)--Tufts University, 2022.; Submitted to the Dept. of Psychology.; Advisor: Nathan Ward.; Committee: Grace Giles, Heather Urry, and Holly Taylor.; Keywords: Experimental psychology, Cognitive psychology, and Psychology.